Diseño de un plan estratégico para una empresa comercializadora de útiles y equipos de computo caso Serrato Services SAS. (2017)
Nowadays, in the face of the constant expectation in which small and medium-sized companies live, it is necessary to be at the competitive level of large companies and seek to solve organizational problems and focus on planning in order to provide the company with an effective and efficient address. according to what you have. In this work, a strategic planning design was carried out for Serrato Services SAS, a family company responsible for the commercialization of materials and office equipment.